The genus Malesherbia Ruiz & Pav. (Passifloraceae) in Chile - Bull-Hereñu, Kester (Phytotaxa, 2020)
We present here an updated classification of Malesherbia taxa native to Chile including 14 species and 10 varieties, of which 9 species and 9 varieties are endemic to the territory. Distributional and nomenclature adjustments have been adopted following a combination of literature and herbarium revisions, field observations and additional collections. We include the description of two new varieties, reinstatement of M. solanoides and M. bracteata, and new combinations in section Xeromantana.